LEGAL ANALYSIS OF UNREGISTERED MARRIAGE VIEWED FROM ULAMA’S PERSPECTIVE IN ACEH PROVINCE - Iman Jauhari; Azhari Yahya; Darmawan Darmawan; Dahlan Dahlan; Muhammad Nasir (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2023)
The purpose of this study is to scrutinize the legal analysis of unregistered marriage, to identify the factors that cause unregistered marriages, and to analyze the views of ulama about unregistered marriage in Aceh. The method used in this research is an empirical juridical method with a qualitative approach. This research was conducted in Aceh and data collection was carried out by means of field research supported by library research. The results show that marriage registration has been regulated in the Marriage Law and in the Islamic Compilation Law as well as a set of implementing regulations in the field of marriage registration. The factors that cause unregistered marriage in Aceh among others are economic factors, illegal pregnancy, lack of understanding and awareness about marriage law, prolonged affairs, not having a guardian, avoiding administrative procedures, and avoiding adultery. The Acehnese Ulama say that generally, they accept marriage registration because it has benefits for the family such as registration of children's birth certificates, and family cards as administrative requirements in other legal acts. However, they refuse to register the marriage if it is related to other provisions such as the age of marriage, polygamy permits, and disputes involving the family. Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui analisis hukum nikah sirri, mengidentifikasi faktor-faktor penyebab nikah siri, dan menganalisis pandangan ulama tentang nikah siri di Aceh. Metode yang digunakan dalam penelitian ini adalah metode yuridis empiris dengan pendekatan kualitatif. Penelitian ini dilakukan di Aceh dan pengumpulan data dilakukan melalui penelitian lapangan yang didukung oleh penelitian kepustakaan. Hasil penelitian menunjukkan bahwa pencatatan perkawinan telah diatur dalam Undang-undang Perkawinan dan dalam Kompilasi Hukum Islam serta seperangkat peraturan pelaksanaan lainnya di bidang pencatatan perkawinan. Faktor-faktor yang menyebabkan perkawinan tidak tercatat di Aceh antara lain adalah faktor ekonomi, kehamilan yang tidak sah, kurangnya pemahaman dan kesadaran tentang hukum perkawinan, perselingkuhan yang berkepanjangan, tidak memiliki wali, menghindari prosedur administrasi, dan menghindari zina. Ulama Aceh menerima pencatatan pernikahan karena memiliki manfaat bagi keluarga seperti pencatatan akte kelahiran anak, dan kartu keluarga sebagai syarat administrasi dalam perbuatan hukum lainnya. Namun, mereka menolak pencatatan perkawinan jika dikaitkan dengan ketentuan lain seperti usia perkawinan, izin poligami, dan perselisihan yang melibatkan keluarga. Kata Kunci: Hukum, Pernikahan sirri, Ulama, Aceh, Pandangan.